Reclaiming the conversation: Islamic intellectual tradition in the Malay Archipelago. Edited by Rosnani Hashim. Selangor, Malaysia: The Other Press, 2010, pp. 288. ISBN 978-983-9541-74-8 (Paperback) - Hussien, Suhailah (IIUM Press, 2013)

(untitled)
Islamic education was introduced in the Malay Archipelago with the spread of Islam in the eleventh century C.E. This later developed into a system of Islamic education in the forms of pondok and madrasah. The book under review, Reclaiming the Conversation: Islamic Intellectual Tradition in the Malay Archipelago, examines the efforts of prominent Muslim intellectuals in developing Islamic education, curriculum and institutions particularly in the Malay world. The works and educational reforms of eleven scholars spanning through the nineteenth and twentieth centuries (CE) from three countries in the Malay world were explored. In particular, the book focuses on Shaykh Daud al-Fatani of Pattani in South Thailand, Munshi Abdullah Muhammad Yusof bin Ahmad (Tok Kenali), Shaykh Ahmad al-Hady and Za’ba of Malaya (Peninsular Malaysia), and Shaykh Abd al-Samad al-Palembani, Imam Zarkasyi, Mahmud Yunus, Hamka, Hasyim Asy’ari and Harun Nasution of Indonesia.